Pepsi-Cola Products Phils., Inc.: Strategies plans - San Jose, Manuel L., Jr. (Animo Repository, 1996)
Pepsi-Cola Products Philippines, Inc. (PCPPI) is a franchise of PepsiCola International (PCI), a global company based in New York, USA. It produces, sells, and distributes pepsi products (Pepsi-Cola, Diet Pepsi, Seven-UP, Mirinda, and Mountain Dew). The companys revenue in 1994 is about Mountain Dew). The companys gross revenue in 1994 is about 4 billion pesos (net revenue 3.5 billion pesos), equivalent to 45 million 8-oz case = 24 8 oz servings). It has 20% share of the Philippine softdrink market.